2020
DOI: 10.1111/1346-8138.15698
|View full text |Cite
|
Sign up to set email alerts
|

Deep cutaneous fungal infection by Pleosporales: An exceptional pathogen in tropical Taiwan

Abstract: Deep cutaneous fungal infections (DCFI) are cutaneous and subcutaneous infectious diseases caused by fungi. Multiple genera of pathogenic fungi have been reported to cause DCFI. Herein, we report three rare cases of Pleosporales deep cutaneous infection in a southern Taiwan medical center. We evaluated the clinical manifestations, histopathological findings, pathogens, treatments and outcomes. The patients were a 77‐year‐old woman, a 78‐year‐old woman and an 81‐year‐old man, who lived in rural tropical areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Although saliva and feces contained Candida , our results suggested that the subgingival plaques might be more suitable for the colonization of Candida organisms because of their higher relative abundance, especially Candida albicans . The largest order under Dothideomycetes was Pleosporales , which was reported to be associated with skin infection ( 32 , 33 ) and also had a higher relative abundance in subgingival plaques than in saliva and feces in our results. Saccharomyces cerevisiae , a prominent fungal species in the human gut ( 26 , 34 ), was more abundant in feces than in saliva and subgingival plaques in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Although saliva and feces contained Candida , our results suggested that the subgingival plaques might be more suitable for the colonization of Candida organisms because of their higher relative abundance, especially Candida albicans . The largest order under Dothideomycetes was Pleosporales , which was reported to be associated with skin infection ( 32 , 33 ) and also had a higher relative abundance in subgingival plaques than in saliva and feces in our results. Saccharomyces cerevisiae , a prominent fungal species in the human gut ( 26 , 34 ), was more abundant in feces than in saliva and subgingival plaques in our study.…”
Section: Discussionsupporting
confidence: 61%
“…These 52 cases corresponded to 38 cases of PHM, including ours [ 1 , 2 , 3 , 4 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and 14 cases of eumycetoma [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Two cases published as mycetoma by Thiyagarajan et al and Sum et al [ 20 , 21 ] were classified in this review as PHM, regarding the clinical presentation and the lack of grains and bone involvement.…”
Section: Methodsmentioning
confidence: 88%
“…Subcutaneous PHM is, as shown in our literature review, the most frequently reported clinical presentation (65% of the literature review cases). It is responsible for nodulocystic subcutaneous lesions and abscesses affecting mostly immunocompromised patients with an immunosuppression course ranging from one month to many years [ 1 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. In addition to this typical subcutaneous form of M. romeroi PHM, other presentations were rarely reported, including superficial, disseminated, ocular, and osteoarticular forms.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) [original Figure 1A ]) (C) Sporotrichoid nodules lesions on the left forearm. (Reproduced from reference Yu et al. (2021) [original Figure 1D ]) (D) Swelling erythematous erosions and necrosis on the left little finger.…”
Section: Resultsmentioning
confidence: 99%
“…(2008) [original Figure 1 ]; (C) : Reproduced from reference Lin et al. (2010) [original Figure 1A ]); (D–F) Moderate forms ( (D) : Reproduced from reference Liu et al (2013) [original Figure 1 ]; (E) : Reproduced from reference Yu et al. (2021) [original Figure 1G ]; (F) : Reproduced from reference Lv et al.…”
Section: Resultsmentioning
confidence: 99%